Analisis RME Pendaftaran Rawat Jalan Menggunakan Metode EUCS di RSUD Dr. Soegiri Lamongan - Adinda Aulia Kusuma Rahayu; Fita Rusdian Ikawati; Lilik Afifah (ARTERI : Jurnal Ilmu Kesehatan, 2026)
The use of Electronic Medical Record System (RME) in healthcare facilities has the main goal of improving the efficiency, accuracy, and quality of services provided to patients. Nonetheless, the successful implementation of this system depends heavily on the level of satisfaction of the end user, who in this case is the officer who operates the system. This study aims to analyze the satisfaction of outpatient enrollment officers with the use of the RME system in the patient enrollment section by adopting the End-User Computing Satisfaction (EUCS) approach as the analytical framework. This research was carried out at Dr. Soegiri Lamongan Hospital using a qualitative research method involving two outpatient registration officers as the main informants. Data collection was carried out through in-depth interviews and observations to obtain comprehensive information about the user experience in using the RME system. The results show that user dissatisfaction is most prominent in the format and timeliness dimensions. The interface display that is considered too congested and the delay in the data validation process are significant obstacles in the workflow of registration officers. As a solution, this study proposes a simplification of the user interface designed to speed up the process of verifying patient data. The interface design improvements are expected to improve the user experience so that outpatient registration officers can work more efficiently. Thus, the implementation of these improvements is expected to be able to support the implementation of more optimal health services and oriented towards user satisfaction